2010
DOI: 10.1007/s11095-010-0149-z
|View full text |Cite
|
Sign up to set email alerts
|

Mannan-Modified Solid Lipid Nanoparticles for Targeted Gene Delivery to Alveolar Macrophages

Abstract: These results demonstrated the active targeting ability of this kind of mannan-modified DNA-loaded vehicles, which may have great potential for targeted gene delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(82 citation statements)
references
References 38 publications
0
82
0
Order By: Relevance
“…So nanoparticles (5200 nm) can significantly accumulate in tumor by ''filtration'' mechanism (Xu et al, 2009). Small particles are also minimal endocytosis by macrophages, so destruction and clearance could be minimized (Yu et al, 2010). A mean diameter lower than 200 nm and a PDI lower than 0.2 were considered desirable to propose the formulation for in vitro and in vivo experiments (Accardo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…So nanoparticles (5200 nm) can significantly accumulate in tumor by ''filtration'' mechanism (Xu et al, 2009). Small particles are also minimal endocytosis by macrophages, so destruction and clearance could be minimized (Yu et al, 2010). A mean diameter lower than 200 nm and a PDI lower than 0.2 were considered desirable to propose the formulation for in vitro and in vivo experiments (Accardo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The IC 50 value of RGD-TMZ/NLCs was 2-fold over RGD-TMZ/NLCs and 10-fold over TMZ solution in reducing viability of malignant glioma cells, accounting for the highest antitumor activity. Cytotoxicity deeply influenced the ability of the nanocarriers (Yu et al, 2010). The results demonstrated the higher cytotoxicity of NLCs formulas than free drug solution.…”
Section: In Vitro Cytotoxicitymentioning
confidence: 95%
“…[20][21][22] Stearic acid 50 mg and injectable soya lecithin 30 mg were accurately weighed and dissolved in 10 mL of acetone. The organic phase was added dropwise into the 0.2% dimethyldioctadecylammonium bromide solution, under stirring at 600 rpm and at room temperature.…”
Section: Preparation Of Cationic Slnmentioning
confidence: 99%
“…19 It has been shown that human and murine macrophages express the mannose receptor on their surface, and several studies have confirmed the feasibility of using mannose or mannan-modified nanocarriers to target macrophages. 20 In the present study, a novel conjugated ligand, mannanpolyethylene glycol-L-α-phosphatidylethanolamine (MN-PEG-PE) was synthesized, and MN-PEG-PE-modified SLN were investigated. In this study we compared the two strategies for modification using the same ligands (MN-PEG-PE) in an attempt to identify which kind of nanomedicine is preferable for targeted gene therapy, ie, premodified or postmodified gene-loaded SLN/DNA.…”
Section: Introductionmentioning
confidence: 99%